The determinant of capital structure among construction companies in Malaysia / Ainul Azrul Azman - Azman, Ainul Azrul (2013)
This study was attempted to identify the determinant of the capital structure among construction companies in Malaysia. The dependent variable in this study is debt ratio while the independent size of firm, profitability and firm reputation. All data is collected from UiTM Database which is OSIRIS. The data collected from 36 companies for 10 years (2002 - 2011). Besides, the study was being tested using Pooled Ordinary Least Square Regression ( OLS ), Random Effect (Breush and Pagan Test) and Random Generalized Least Square Regression (GLS) to analyze all the data. The finding shows that profitability is not significant with debt ratio but other variables which is size of firm and reputation shows significant with debt ratio.